Changes in seed quality during seed development and maturation in maize. - Mendoza-Elos, Mariano; Latournerie, Luis; Moreno, Ernesto; Castañón, Guillermo; Cruz-Carrillo, José; De León, Carlos; García, J. Guadalupe (Agronomía Mesoamericana, 2004)
The objective of present study was determine the changes in seed developing and maturation on germination, seedling vigor, volumetric weight and weight of 1000 seeds. The experimental study was carried out at Celaya, Guanajuato, Mexico during 2001. The variety used in this study was sown at a rate of two seeds per hill in two replications of two rows of five meters long and spaced 0.75 meters. Sampling was started 30 days after female flower appearance then taking eight ears per treatment that were manually shelled. Average values for germination and seedling vigor showed the same behavior as indicatiors of seed ripening. Volumetric weight was increased to 71 kg/ha at 130 days after planting. No significant effect was found on seed physiological quality due to 1000 seeds weight. The greatest seed germination percentage and seedling vigor was found when seed humidity was reduced from 40 to 20 %. Samples taken 106 and 121 days after sowing were poor indicators of seed quality. Also the greatest vigor and seed germination was found in the basal part of the ears. These results show that physiologic maturity is not the best indicator for maximum seed quality but dry matter accumulation.